Landscape management and domestication of Stenocereus pruinosus (Cactaceae) in the Tehuacán Valley: human guided selection and gene flow - Parra Fabiola; Blancas José; Casas Alejandro (BMC, 2012)
Abstract Background Use of plant resources and ecosystems practiced by indigenous peoples of Mesoamerica commonly involves domestication of plant populations and landscapes. Our study analyzed interactions of coexisting wild and managed populations of the pitaya Stenocereus pruinosus, a columnar cactus used for its edible fruit occurring in natural forests, silviculturally managed in milpa agroforestry systems, and agriculturally managed in homegardens of the Tehuacán Valley, Mexico. We aimed at analyzing criteria of artificial selection and their consequences on phenotypic diversity and differentiation, as well as documenting management of propagules at landscape level and their possible contribution to gene flow among populations. Methods Semi-structured interviews were conducted to 83 households of the region to document perception of variation, criteria of artificial selection, and patterns of moving propagules among wild and managed populations. Morphological variation of trees from nine wild, silviculturally and agriculturally managed populations was analyzed for 37 characters through univariate and multivariate statistical methods. In addition, indexes of morphological diversity (MD) per population and phenotypic differentiation (PD) among populations were calculated using character states and frequencies. Results People recognized 15 pitaya varieties based on their pulp color, fruit size, form, flavor, and thorniness. On average, in wild populations we recorded one variety per population, in silviculturally managed populations 1.58 ± 0.77 varieties per parcel, and in agriculturally managed populations 2.19 ± 1.12 varieties per homegarden. Farmers select in favor of sweet flavor (71% of households interviewed) and pulp color (46%) mainly red, orange and yellow. Artificial selection is practiced in homegardens and 65% of people interviewed also do it in agroforestry systems. People obtain fruit and branches from different population types and move propagules from one another. Multivariate analyses showed morphological differentiation of wild and agriculturally managed populations, mainly due to differences in reproductive characters; however, the phenotypic differentiation indexes were relatively low among all populations studied. Morphological diversity of S. pruinosus (average MD = 0.600) is higher than in other columnar cacti species previously analyzed. Conclusions Artificial selection in favor of high quality fruit promotes morphological variation and divergence because of the continual replacement of plant material propagated and introduction of propagules from other villages and regions. This process is counteracted by high gene flow influenced by natural factors (pollinators and seed dispersers) but also by human management (movement of propagules among populations), all of which determines relatively low phenotypic differentiation among populations. Conservation of genetic resources of S. pruinosus should be based on the traditional forms of germplasm management by local people.